2002
DOI: 10.1038/sj.bjp.0704539
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of cardiac fibrosis by pirfenidone and amiloride in DOCA‐salt hypertensive rats

Abstract: 1 This study has administered pirfenidone (5-methyl-1-phenyl-2-[1H]-pyridone) or amiloride to attenuate the remodelling and associated functional changes, especially an increased cardiac stiness, in DOCA-salt hypertensive rats. body wt) without lowering systolic blood pressure. 4 Collagen deposition was signi®cantly increased in the interstitium after 2 weeks and further increased with scarring of the left ventricle after 4 weeks; pirfenidone and amiloride reversed the increases and prevented further increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 31 publications
8
87
0
2
Order By: Relevance
“…In their study, pirfenidone treatment resulted in a significant reduction of atrial fibrosis. Mirkovic et al 11 reported that pirfenidone reverses and prevents cardiac remodeling as well as increased cardiac stiffness in deoxycorticosterone acetate-salt hypertensive rats. Those results suggest a broad effect of pirfenidone on potent profibrotic mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, pirfenidone treatment resulted in a significant reduction of atrial fibrosis. Mirkovic et al 11 reported that pirfenidone reverses and prevents cardiac remodeling as well as increased cardiac stiffness in deoxycorticosterone acetate-salt hypertensive rats. Those results suggest a broad effect of pirfenidone on potent profibrotic mediators.…”
Section: Discussionmentioning
confidence: 99%
“…The Ang II/AT1 receptor interaction generates an immediate calcium-dependent response and late nuclear factor-kB activation through the activation of different pathways, including protein kinase C, mitogen-activated protein kinase cascades, receptor tyrosine kinases and non-receptor tyrosine kinases. 2,4 Pirfenidone (5-methyl-1-phenyl-2-[ 1 H]-pyridone) has been shown to reduce the fibrosis of different organs (for example, lung 5,6 kidney 7-9 liver, 10 heart [11][12][13] ) and vascular remodeling 14 through its inhibitory effect on fibroblast growth and collagen synthesis, which is achieved by reducing the expression of profibrotic cytokines (for example, TGF-b 15,16 ). Furthermore, pirfenidone has been successfully used in a double-blind, placebo-controlled trial focused on patients with idiopathic pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Pirfenidone is a recently developed broad spectrum antifibrotic agent with efficacy in preventing and resolving several kinds of fibrotic disease, including lung (11) and renal fibrosis (13), liver cirrhosis (15), cardiac remodeling, and increased cardiac stiffness (36). Several recent studies have been published about the efficacy of pirfenidone on idiopathic pulmonary fibrosis (IPF).…”
Section: Discussionmentioning
confidence: 99%
“…Although some drugs interfering with TGF-␤ expression (i.e., pirfenidone and tranilast) have shown promising antifibrotic effects in animal models of hypertension (30,44), no evidence has been provided yet that this is due to the reduced expression of LOX. In contrast, the chronic in vivo blockade of the TGF-␤ type III receptor ␤-glycan with the peptide P144 has been shown to be associated with the reduced expression of LOX mRNA and the precursor and active form of LOX protein, as well as with the decrease in collagen cross-linking and deposition in the myocardium of treated SHRs (24).…”
Section: Therapeutic Modulation Of Lox In Cardiac Diseasesmentioning
confidence: 99%